Not in my book : a novel - Holt, Katie (Fiction writer) (Alcove Press, 2024)
When romance novelist Rosie and ex-crush literary fiction writer Aiden must cowrite a novel blending genres, the reluctant duo's accidentally steamy novel provides an outlet for their attraction to each other--but will a career-changing opportunity reignite their rivalry and threaten their love story?